1993
DOI: 10.1152/ajpheart.1993.265.2.h509
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in endothelium-dependent hyperpolarization in the rat mesenteric artery

Abstract: This study was designed to determine the age-related changes in the endothelium-dependent hyperpolarization to acetylcholine (ACh) and its contribution to relaxation in the isolated mesenteric artery from normotensive and hypertensive rats. Membrane potentials and contractions were recorded in arteries from male Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR) that were 5-6 wk old (young), 6-8 mo old (adult), and 20-26 mo old (aged). Endothelium-dependent hyperpolarizations produced by ACh, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
65
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 0 publications
8
65
4
Order By: Relevance
“…Endothelium-dependent hyperpolarization decreases with increasing age, even in normotensive rats. 25 The underlying mechanisms by which drug therapy improved the EDHF-mediated hyperpolarization are not known from the present study, but we can speculate about several mechanisms. Because hyperpolarization in response to levcromakalim, a direct activator of ATP-sensitive K ϩ channels, 38 was not modulated by antihypertensive treatment, alteration in smooth muscle properties may not be involved.…”
Section: Effects Of Antihypertensive Treatments On Edhf-mediated Hypementioning
confidence: 68%
See 2 more Smart Citations
“…Endothelium-dependent hyperpolarization decreases with increasing age, even in normotensive rats. 25 The underlying mechanisms by which drug therapy improved the EDHF-mediated hyperpolarization are not known from the present study, but we can speculate about several mechanisms. Because hyperpolarization in response to levcromakalim, a direct activator of ATP-sensitive K ϩ channels, 38 was not modulated by antihypertensive treatment, alteration in smooth muscle properties may not be involved.…”
Section: Effects Of Antihypertensive Treatments On Edhf-mediated Hypementioning
confidence: 68%
“…10,35,37 We previously showed that ACh-induced hyperpolarization and relaxation via EDHF are markedly impaired in the arteries of 6-to 8-month-old SHRs compared with age-matched WKYs. 10,25 Van de Voorde et al 24 reported an impairment of endothelium-dependent hyperpolarization in response to carbachol in the aortas of rats with renal hypertension. Endothelium-dependent hyperpolarization decreases with increasing age, even in normotensive rats.…”
Section: Effects Of Antihypertensive Treatments On Edhf-mediated Hypementioning
confidence: 99%
See 1 more Smart Citation
“…Other risk factors for atherothrombotic cardiovascular disease have also been reported to affect the EDHF pathway, including hypertension, 17,18 hypercholesterolemia, 19 diabetes mellitus, 12 and aging. 20 Interference with the integrity of the EDHF pathway may thus be a final common pathway through which these risk factors cause microangiopathy and end-organ damage. In conclusion, EDHF-mediated vasodilation is impaired in the renal microcirculation of acute and chronically hyperhomocysteinemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The higher susceptibility of the vasculature in the aged SHR to ischemia may also be responsible for the impaired vasodilatation in the recovery periods. Age-related impairment of dilatory functions of ves sels in both normotensive rats and SHR (Mayhan et al , 1990;Fujii et al , 1993) has been reported.…”
Section: Discussionmentioning
confidence: 99%